StuditentangFaktorIndividu, LingkunganKerja, Komputer, danKeluhanComputer Vision Syndrome (CVS) padaPenggunaKomputerdi PerusahaanPerakitan Mobil - Maryah Ulpah; Hanifa Maher Denny; Siswi Jayanti (Jurnal Kesehatan Masyarakat (Undip), 2017)
Computer Vision Syndrome is a group of eye problems related to computer usage. The symptoms of CVS including the eye strain, headaches, blurred vision, dry and irritated eyes, red eyes, sore neck and back, eyes are too sensitive to light, and double vision. CVS can be caused by a variety of individual factors, work environment, and computer. The purpose of this research is to determine the factors associated with CVS on computer users in a car assembling company. This type of research is a quantitative study with cross sectional approach. Population in this research were computer users in a car assembling company that amounted to 74 people. Samples were choosen with the inclusion criteria (understood about Indonesian language, male, did not have history of diabetes and hypertension, were willing to be respondent, and not currently on leave) so that was conducted there were 41 people as respondents. Bivariate analysis results with Rank Spearman correlation indicate that there was a correlation between the long break after using the computer (p-value = 0,035), knowledge of CVS (p-value = 0,041), and local lighting intensity (p-value = 0,030), and there was no correlation between age (p-value = 0,481), the work of computer usage (p-value = 0,269), the duration of use of the computer (p-value = 0,360), distance vision of computers (p-value = 0,206), and the point of view of the computer (p-value = 0,063). From the results of this research it could be concluded that there was a correlation between the long break after using computers, knowledge of CVS, and the intensity of the illumination with local complaints of CVS. Researchers suggest that the company should give the lighting intensity that complies with the standards, establish a policy of using maximum breaks, give knowledge about CVS. Advice for computer user to apply the rule of 20-20-20. As well as on other researchers to analyze other variables thought to be associated with complaints of CVS.